Keller - Gordon, Kim 1953- (Karma, 2024)
"This volume is an intimate consideration of musician Kim Gordon’s brother’s life and art featuring personal photographs and pages from his journals. Following Keller Gordon’s death in 2023, his sister collected mementos—relics from a shared existence spent dipping in and out of one another’s lives over decades—including drawings, photos, poems and the diaries he kept at various stages of lucidity. The Sonic Youth frontwoman also authored a diaristic essay about their childhood, the complexities of family dynamics and the double-edged sword of creating and maintaining legends about those we love and admire. "I know exactly when the myth of my brother started," she writes. Designed to evoke the format of Keller’s diaries, this volume features facsimiles of his writings, offering insight into the complicated figure of Keller Gordon as well as his sister’s life. Through Kim’s prose and Keller’s own words, Keller extends and destabilizes the form of the biography, foregrounding the fragmented and the imperfect, echoing how memories themselves dissolve and take new shape over time." -Publisher
Edition of 1500
Keywords: Gordon, Kim -- 1953-; Bruder -- Motiv; Gordon, Kim / 1953-; Gordon, Keller / Diaries; Schizophrenics / Diaries; Schizophrenics / Family relationships; Siblings of people with disabilities; Schizophrènes / Journaux intimes; Schizophrènes / Relations familiales; Frères et surs de personnes handicapées; Gordon, Kim / 1953- / https://id.oclc.org/worldcat/entity/E39PBJkpb48qbJDVykKqF9yWXd; Schizophrenics; Diaries; ART / Individual Artists / Artists' Books; Künstlerbuch